What Matters? Changes in European Youth Participation - Gozzo, Simona; Sampugnaro, Rossana (PARTECIPAZIONE E CONFLITTO, 2017)
During the twentieth century, theoretical and empirical studies aimed to analyse changes in individual participation and in social and political dynamics. A great emphasis was attributed to the process of individualization. Young people were described as a generation with a limited political involvement, especially considering traditional forms of political participation, but more and more likely to search an “individualized” way towards the participation. Furlong and Cartmel bring back the youth identity to the thesis about the reflexive rebuilding of identity, according to which the individualization is a process due to some structural characteristics of post-industrial society. Employing data from European Values Study researches, we test if and how structural variables and contextual dynamics affect political involvement and its changes, with particular attention on youth involvement. Actually, participation takes the form of a multifaceted reality and youth individual profiles are heterogeneous. The process of individualization has, in this sense, different effects and various consequences on participation’s profiles. According to these considerations, this analysis shows the incidence of structural, contextual and cognitive dimensions on individual choices to participate, focusing on longitudinal plan and cohorts. A second step compares the causal importance of structural and cognitive dimension on different typologies of involvement.